Program Pesantren Kilat Sebagai Upaya Meningkatkan Pemahaman Agama Islam Bagi Anak-Anak (Studi Pada Desa Sukarema, Kecamatan Lenek, Kabupaten Lombok Timur) - Wahyu Trisno Aji (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Studying religious knowledge is very important for Muslims. Because studying religious knowledge can get two benefits at once, namely the advantage of understanding the world with the guidelines of Islamic teachings as well as a promise from Allah SWT for students of knowledge will get the best place in heaven. The Lightning Islamic Boarding School is an educational program created by young people at the Aqo’idul Iman Sukarema Mosque while also working with KKP UIN Mataram students whose main goal in this program is to cultivate, improve, provide understanding, knowledge and teachings of the Islamic religion in the educational space of the Islamic boarding school system within a certain period of time. The Lightning Islamic Boarding School was created as a flagship program for KKP UIN Mataram students by guiding and teaching Sukarema village children in learning religious knowledge in a concise yet easy to understand way. Producing intelligent successors to science as well as actualizing it in life. The Lightning Islamic Boarding School program is important to increase the enthusiasm of the children in Sukarema Village for motivation in studying religion and at the same time increasing worship every day. Keywords: Islamic boarding school, KKP UIN Mataram